반응표면분석법을 이용한 넙치 첨가 어묵면의 품질 특성 및 제조조건 최적화 - 오정환(Jung Hwan Oh); 김형광(Hyung Kwang Kim); 유가현(Ga Hyun Yu); 정경임(Kyong Im Jung); 김세종(Se Jong Kim); 정준모(Jun Mo Jung); 천지현(Ji Hyeon Cheon); Fatih Karadeniz; 공창숙(Chang-Suk Kong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
The purpose of this study was to optimize the formulation for fish-meat noodles added with farmed olive flounder (Paralichthys olivaceus) using response surface methodology. Fish-meat (surimi) from P. olivaceus was prepared by a traditional washing process. Independent variables were Alaska pollack, fish-meat from P. olivaceus, and starch, whereas dependent variables were whiteness and texture. The results for whiteness and texture produced very significant values for whiteness (P<0.001), strength (P<0.001), hardness (P<0.05), breaking force (P<0.001), chewiness (P<0.001), brittleness (P<0.001), extensibility force (P<0.001), and extensibility distance (P<0.05). The optimal formula for fish-meat noodle was addition of 72.00 g Alaska pollack, 11.59 g P. olivaceus, and 15.86 g starch. Experimental values of whiteness, strength, hardness, breaking force, chewiness, brittleness, extensibility force, and extensibility distance under optimal conditions were $59.01{±}0.53$, $708.22{±}54.12g/cm^2$, $1,390.07{±}67.70g/cm^2$, $3,622.77{±}92.52g$, $2,686.94{±}103.22g$, $278,578.31{±}10,150.22g$, $52.22{±}2.97g$, $24.14{±}3.55mm$, respectively. 본 연구에서는 반응표면분석법을 이용하여 어묵면의 주원료인 넙치, 명태, 전분의 함량이 어묵면의 품질에 미치는 영향을 분석하고 어묵면의 배합비를 최적화하였다. 반응모형에서 명태와 넙치의 함량이 높을수록 어묵면의 백색도, 강도, 경도, 파괴강도, 변형도, 씹힘성, 깨짐성, 신장력, 신장거리가 증가하였고, 전분의 함량이 높을수록 감소하거나 그 영향이 미미한 것으로 나타났다. 양식산 넙치를 첨가한 어묵면의 주원료 배합비의 최적조건은 명태, 넙치, 전분의 함량이 각각 명태 72.00 g, 넙치 11.59 g 전분 15.86 g인 것으로 나타났으며, 이때의 만족도는 0.9558이었다, 이들 배합비를 적용하여 넙치 첨가 어묵면을 제조한 결과 백색도는 $59.01{±}0.53$, 강도 $708.22{±}54.12g/cm^2$, 경도 $1,390.07{±}67.70g/cm^2$, 파괴강도 $3,622.77{±}92.52g$, 씹힘성 $2,686.94{±}103.22g$, 깨짐성 $278,578.31{±}10,150.22g$, 신장력 $52.22{±}2.97g$, 신장거리 $24.14{±}3.55mm$로 나타났다. 이상의 결과로부터 넙치 첨가 어묵면 제조에 있어서 명태, 넙치, 전분의 배합비를 최적화함으로써 품질이 우수한 고부가가치 연제품으로서의 어묵면 제품화가 가능할 것으로 생각된다.